Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2011)
3 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2011)
22 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G.; Walker, Harry (Journal of Special Education Technology, 2011)
22 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Effects of varied levels of treatment integrity on appropriate toy manipulation in children with autism - Groskreutz, Nicole C.; Groskreutz, Mark P.; Higbee, Thomas S. (Research in Autism Spectrum Disorders, 2011)
We assessed the effects of varying the treatment integrity of a prompting procedure on appropriate toy manipulation in two preschool-aged children with autism. Following an assessment to identify toys with high levels of inappropriate toy manipulation, each of three toys was associated with implementation of the prompting procedure at a different integrity level (10%, 50%, or 100%). For one participant, only the 100% integrity condition produced increases in appropriate toy manipulation. For the second participant, both the 50% and 100% integrity conditions produced increases in appropriate toy manipulation. These results suggest that integrity errors negatively impacted the acquisition of appropriate toy manipulation in children with autism, although the necessary level of treatment integrity varied across participants. (C) 2011 Elsevier Ltd. All rights reserved.
15 citations (Crossref) [2023-10-31] tex.researcherid-numbers: Higbee, Thomas S/F-5157-2010 tex.unique-id: ISI:000292235600009
Keywords: Autism; Play skills; Toy manipulation; Treatment integrity; article; autism; case report; child; dept.sed; human; learning; machiavellianism; male; play therapy; preschool child; priority journal; psychologic assessment; treatment planning

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Citation Key Alias: lens.org/104-519-704-094-108
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed